NILAI EKONOMI MUSEUM ULLEN SENTALU DENGAN TRAVEL COST DAN CONTINGENT VALUATION METHOD TAHUN 2012 - , Fina Sugriani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research combined the travel cost method and contingent valuation method to estimate the economic value of Museum of Culture and Art Ullen Sentalu, Yogyakarta. Currently Museum Ullen Sentalu is enhancing its popularity through the increase of the number and quality of its facilities and developing new concept of museum (living museum) to enhance the tourism attraction. To conduct the research, the travel cost method was applied by using the count data regression, and the contingent vauluation method was applied by using the ordinary least square.The visitorsâ reaction to the ticket price enhancement as the implication of the increase of museumsâ quality was also observed. Based on the analysis result, the economic value of Museum Ullen Sentalu using the travel cost method was ranged for Rp4.325.031.904,00 - Rp18.844.810.920,00. Meanwhile the willingness to pay value by using the contigent valuation method was ranged for Rp179.785.000,00 - Rp1.797.850.000,00. Factors that significantly affect the number of visits to the museum were travel cost, income, age, and the visitorâs perception about the environment quality of the museum. However, the visitors reacted positively to the ticket price enhancement assumption, only if there is enhancement of its facilities and accessibility of the museum